An International Adult Guideline for Making Clozapine Titration Safer by Using Six Ancestry-Based Personalized Dosing Titrations, CRP, and Clozapine Levels - de Leon, Jose; Schoretsanitis, Georgios; Smith, Robert L; Molden, Espen; Solismaa, Anssi; Seppälä, Niko; Kopeček, Miloslav; Švancer, Patrik; Olmos, Ismael; Ricciardi, Carina; Iglesias-Garcia, Celso; Iglesias-Alonso, Ana; et al. (Pharmacopsychiatry, 2022)
This international guideline proposes improving clozapine package inserts worldwide by using ancestry-based dosing and titration. Adverse drug reaction (ADR) databases suggest that clozapine is the third most toxic drug in the United States (US), and it produces four times higher worldwide pneumonia mortality than that by agranulocytosis or myocarditis. For trough steady-state clozapine serum concentrations, the therapeutic reference range is narrow, from 350 to 600 ng/mL with the potential for toxicity and ADRs as concentrations increase. Clozapine is mainly metabolized by CYP1A2 (female non-smokers, the lowest dose; male smokers, the highest dose). Poor metabolizer status through phenotypic conversion is associated with co-prescription of inhibitors (including oral contraceptives and valproate), obesity, or inflammation with C-reactive protein (CRP) elevations. The Asian population (Pakistan to Japan) or the Americas' original inhabitants have lower CYP1A2 activity and require lower clozapine doses to reach concentrations of 350 ng/mL. In the US, daily doses of 300-600 mg/day are recommended. Slow personalized titration may prevent early ADRs (including syncope, myocarditis, and pneumonia). This guideline defines six personalized titration schedules for inpatients: 1) ancestry from Asia or the original people from the Americas with lower metabolism (obesity or valproate) needing minimum therapeutic dosages of 75-150 mg/day, 2) ancestry from Asia or the original people from the Americas with average metabolism needing 175-300 mg/day, 3) European/Western Asian ancestry with lower metabolism (obesity or valproate) needing 100-200 mg/day, 4) European/Western Asian ancestry with average metabolism needing 250-400 mg/day, 5) in the US with ancestries other than from Asia or the original people from the Americas with lower clozapine metabolism (obesity or valproate) needing 150-300 mg/day, and 6) in the US with ancestries other than from Asia or the original people from the Americas with average clozapine metabolism needing 300-600 mg/day. Baseline and weekly CRP monitoring for at least four weeks is required to identify any inflammation, including inflammation secondary to clozapine rapid titration.
Keywords: antipsychotika; C-reaktivní protein; kyselina valproová; Asian People; mužské pohlaví; C-Reactive Protein; ženské pohlaví; dospělí; Humans; Adult; Clozapine; Female; Antipsychotic Agents; klozapin; Valproic Acid; Asijci; lidé; Male